2012
DOI: 10.1080/13607863.2012.688193
|View full text |Cite
|
Sign up to set email alerts
|

The association of mental conditions with blood glucose levels in older adults with diabetes

Abstract: Objectives People with diabetes must engage in several self-care activities to manage blood glucose; cognitive function and other affective disorders may affect self-care behaviors. We examined the executive function domain of cognition, depressive symptoms, and symptoms of generalized anxiety disorder (GAD) to determine which common mental conditions that can co-occur with diabetes are associated with blood glucose levels. Methods We conducted a cross-sectional in-person survey of 563 rural older adults (ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 57 publications
2
27
0
1
Order By: Relevance
“…Individuals with DM in both the SAS and MCSA samples demonstrated considerably worse performance in executive function compared to non-DM participants, consistent with previous reports [1,30,31]. In a large sample of 1900 non-demented people in a population-based study, subjects with diagnosed diabetes had worse executive function and slower processing speed compared to normoglycemics [32] In a cross-sectional study of 563 elderly diabetics, decreasing hemoglobin A1c level was associated with improvement in executive function [ [1,30,31]; the study did not include non-diabetics as in the present study thus the estimates magnitude of the differences may have been biased toward the null. In small study (n=40) of elderly diabetics and non-diabetics (a convenience sample), diabetics performed worse on the test of executive function compared to non-diabetics [33].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Individuals with DM in both the SAS and MCSA samples demonstrated considerably worse performance in executive function compared to non-DM participants, consistent with previous reports [1,30,31]. In a large sample of 1900 non-demented people in a population-based study, subjects with diagnosed diabetes had worse executive function and slower processing speed compared to normoglycemics [32] In a cross-sectional study of 563 elderly diabetics, decreasing hemoglobin A1c level was associated with improvement in executive function [ [1,30,31]; the study did not include non-diabetics as in the present study thus the estimates magnitude of the differences may have been biased toward the null. In small study (n=40) of elderly diabetics and non-diabetics (a convenience sample), diabetics performed worse on the test of executive function compared to non-diabetics [33].…”
Section: Discussionsupporting
confidence: 80%
“…We observed a mild to moderate detrimental effect of DM on cognition, with the effect sizes ranging from 0.10-0.25 standard deviation (SD). This is slightly lower than reported for hospital-based studies [31,42], and is understandable considering the potential sample selection bias in clinic-based studies that typically include subjects with more severe disease. Moreover, according to our previous comparison between the participants and nonparticipants in the two study samples [12,13], the non-participants or telephone-interviewed subjects were older and had more vascular comorbidities which would have biased our estimates.…”
Section: Discussionmentioning
confidence: 50%
“…The current study is based on data collected in the second project phase. Key features of the study design, including recruitment and data collection procedures are described elsewhere 8,14,15 and summarized here.…”
Section: Methodsmentioning
confidence: 99%
“…Animal studies in rodents with streptozotocin-induced diabetes (T1DM model) have demonstrated structural changes in grey and white matter, dendritic atrophy in the CA3 hippocampal pyramidal neurons and neurobehavioral deficits associated with impaired hippocampal long-term potentiation (10,11). T2DM patients have also been found to have specific and global cognitive deficits in psychomotor speed, executive functions, memory skills, verbal fluency, attention and visuospatial abilities (12,13,14). Longitudinal studies have identified significantly higher risk of developing dementia or cognitive decline in diabetic patients and also suppose the link between T2DM and the risk of Alzheimer's disease (AD) (15,16).…”
Section: Introductionmentioning
confidence: 98%